2013
DOI: 10.1186/1477-7819-11-51
|View full text |Cite
|
Sign up to set email alerts
|

Significance of CD133 expression in esophageal squamous cell carcinoma

Abstract: BackgroundCD133 was recently reported to be a cancer stem cell marker and a prognostic marker for several tumors. However, few studies have investigated CD133 expression in esophageal squamous cell carcinoma (ESCC). Therefore, we examined whether CD133 could serve as a prognostic marker of ESCC and investigated the correlation between CD133 expression and the clinicopathological findings of ESCC patients and several markers.MethodsWe studied 86 ESCC patients who underwent curative surgery without neoadjuvant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…Accumulated studies have reported CD133 as a marker for CSCs in various cancers. [4][5][6][7][8][9][10][11][12] Our data showed that CD133 þ CXCR4 þ cancer cells had a higher proliferative capacity than the other subgroups in ESCC, which is parallel to the characteristics of CSCs. 10 ( Moreover, the receptor for SDF-1, CXCR4, plays an important role in the migration and metastasis in several cancers.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Accumulated studies have reported CD133 as a marker for CSCs in various cancers. [4][5][6][7][8][9][10][11][12] Our data showed that CD133 þ CXCR4 þ cancer cells had a higher proliferative capacity than the other subgroups in ESCC, which is parallel to the characteristics of CSCs. 10 ( Moreover, the receptor for SDF-1, CXCR4, plays an important role in the migration and metastasis in several cancers.…”
Section: Discussionmentioning
confidence: 75%
“…It has been reported to be a marker of CSCs in the brain, colon, pancreas, prostate, liver, lung, kidney, and esophagus. [4][5][6][7][8][9][10][11][12] CXCR4 is a membrane-bound receptor that selectively binds to the CXC chemokine ligand 12, which is also known as stromal cell-derived factor 1 (SDF-1). The CXC chemokine ligand 12/CXCR4 signaling pathway plays an important role in carcinogenesis, progression, and metastasis, which results in decreased overall survival (OS) and poor prognosis.…”
Section: Perspectivementioning
confidence: 99%
“…Thus, assessment of the overexpression and accumulation of mutant p53 protein by immunohistochemistry has been widely used to detect abnormal p53 expression in cancers. Although several studies have examined the relationship between p53 IHC expression and prognosis in ESCC, this work is limited by the small sample size, and the results are controversial [7][8][9][10][16][17][18][19][20][21][22]. We conducted a large-scale study with a long follow-up to examine p53 expression in relation to the clinicopathologic features and prognosis of ESCC.…”
Section: Discussionmentioning
confidence: 97%
“…MMP7 expression was associated with favorable prognosis of malignant neoplasms of ovary and salivary gland [11,20], while in cholangiocarcinoma and esophageal squamous cell carcinoma, CD133 negativity was related to advanced tumor stage and poor prognosis [4,16]. Negative Oct3/4 expression was correlated with invasion depth, lymph node metastasis, and lymphatic invasion of gastric cancer [13].…”
Section: Discussionmentioning
confidence: 99%